DETERMINATION OF THE FUNCTIONAL PROPERTIES OF VARIETIES OF NEW RICE FOR AFRICA (NERICA) RELEVANT TO ITS PROCESSING - Chukwuka, Eze Paul (Journal on Processing and Energy in Agriculture, 2021)
Flour from rice can be applicable into several types of food, or be used directly as a food substitute, and this can have an impact on the final quality of the product. This aimed to determine the functional properties of some selected NERICA varieties, namely, FARO 44, FARO 52, FARO 57, FARO 60 and FARO 61. Results obtained showed that the functional properties, such as the water absorption capacity (WAC), swelling power, water solubility index (WSI), bulk density, oil absorption capacity (OAC), and the foaming capacity, ranged from 251.74 to 298.51 (%); 7.42 to 8.41 (g/g); 10.01 to 12.27 (%); 0.92 to 1.00 (%); 0.45 to 1.36 (%); and 7.29 to 11.76 (%) respectively. All recorded samples were significantly difference (p < 0.05). FARO 61 recorded highest point of 298.51 (%), and 1.36 (%), in WAC and OAC respectively. While FARO 57 recorded the highest swelling power of 8.41 (g/g). These determined results of the functional properties of NERICA flour samples, will be useful in determining their suitability in food and other relevant industries because the flour samples showed high quality range of functional properties that makes them favourable for such activities.